COPING WITH AN ONLINE MENTALITY - DER WEEL, ADRIAAN VAN (Knygotyra, 2014)
In this brief essay I would like to pursue the notion that in the world of books we may be able to observe the clash between publishers catering to conventional reading and buying habits, and the expectations of readers who don’t consider themselves bound by the traditions and customs of the field. If asked, these readers might confess to regarding the traditions and customs of the book trade as antiquated, and no longer relevant in today’s world of instant and constant access to information, and certainly not applicable to them. Publishers have had to adjust their practices to the unfamiliar expectations of a new reading public many times in the history of the book. These changing expectations have concerned both the content (the ‘what’) and the form (the ‘how’) of reading. The mentality in the publishing industry is obviously going to have to reflect all the various mentalities that consumers display, including this pervasive but elusive online mentality. If the analysis I presented in this essay is in any way correct, it follows that there is a need for the book industry, and especially trade publishing to do market research. We clearly cannot speak of a reading crisis, with probably more written information being produced and consumed than ever before in history. But it does appear that a buying crisis is looming in the book industry. The sort of market research that is called for is not the sort that individual publishers should or can perform; it is the sort that policy makers, educationalists, and the book industry need to engage in collectively. For surely it makes sense to find out what various identifiable segments of the market would like to read, and how they would like to access their reading, and how much and how they would be prepared to pay for it.